Ending hunger, increasing incomes, and protecting the climate: What would it cost donors? - Laborde Debucquet, David; Murphy, Sophia; Parent, Marie; Porciello, Jaron; Smaller, Carin (International Institute for Sustainable Development, 2020)
In response to the global commitment to rid the world of hunger, Ceres2030 partnered with Nature Research to answer two linked questions: First, what does the published evidence tell us about agricultural interventions that work, in particular to double the incomes of small-scale producers and to improve environmental outcomes for agriculture? And second, what will it cost governments to end hunger, double the incomes of small-scale producers, and protect the climate by 2030? The project focuses on three of the five targets in the second sustainable development goal (SDG 2, Zero Hunger) and looks at the public spending needed in low- and middle-income countries, including the contribution from donors through official development assistance (ODA) (Laborde et al., 2020). This report answers the second question. The answer to the first question is published as a special collection of Nature Research. This report is published alongside a complementary research project by the Centre for Development Research (ZEF) and the FAO that also identifies high-impact, cost-effective interventions to address the challenges of SDG 2. The use of different research approaches and methodologies helps to identify levels of coherence and strengthens the credibility of proposed policy actions and investments. The approaches show results that are consistent and compatible, confirming that between now and 2030 donors need to double their efforts (von Braun et al., 2020).